2015
DOI: 10.1093/mnras/stv1874
|View full text |Cite
|
Sign up to set email alerts
|

Mass-loss from advective accretion disc around rotating black holes

Abstract: We examine the properties of the outflowing matter from an advective accretion disc around a spinning black hole. During accretion, rotating matter experiences centrifugal pressure supported shock transition that effectively produces a virtual barrier around the black hole in the form of post-shock corona (hereafter, PSC). Due to shock compression, PSC becomes hot and dense that eventually deflects a part of the inflowing matter as bipolar outflows because of the presence of extra thermal gradient force. In ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 113 publications
5
76
0
Order By: Relevance
“…2006) tells us that the essential physics around super-massive and stellar mass BHs are similar. Aktar et al 2015), dissipative flow (Das 2007;, and has also been confirmed in simulations (Molteni et al 1996b;Lee et al 2011;Das et al 2014). The post-shock region of the disc (PSD), has some special properties.…”
Section: Introductionmentioning
confidence: 60%
“…2006) tells us that the essential physics around super-massive and stellar mass BHs are similar. Aktar et al 2015), dissipative flow (Das 2007;, and has also been confirmed in simulations (Molteni et al 1996b;Lee et al 2011;Das et al 2014). The post-shock region of the disc (PSD), has some special properties.…”
Section: Introductionmentioning
confidence: 60%
“…This simplifies the jet structure and make the problem tractable analytically. With these considerations, the jet streamline and the associated cross-section depend on the disc parameters like E and λ, as well as on the spin of the BH, which is a major improvement on the jet geometry assumed in the pseudo-Newtonian regime (Chattopadhyay & Das 2007;Aktar et al 2015). Moreover, the jet solution from the disc is launched with very low velocity along the streamline, but becomes supersonic at a short distance from the base of the jet.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Semi-analytical versions of these studies have been extended into the dissipative regime for flows described by fixed Γ (= cp/cv adiabatic index) equation of state (EoS; Becker et al 2008;Aktar et al 2015), as well as variable Γ EoS . Since shock in accretion is formed close to the central object (r sh < ∼ few×10rs)…”
mentioning
confidence: 99%
“…Further more, we consider the shock to be dissipative in nature and compute the maximum available energy dissipated at the shock. Employing this result, we then calculate the loss of kinetic power from the disc (L max shock ) which could be utilized to power the jets as they are likely to be launched from the PSC (Chakrabarti 1999;Das et al 2001b;Das & Chattopadhyay 2008;Aktar et al 2015). The above analysis apparently provides an estimate which we compare with the jet kinetic power available from observation for six sources and close agreements are seen.…”
Section: Introductionmentioning
confidence: 89%
“…Since PSC is composed with the swarm of hot electrons, soft-photons from the cold preshock matter are inverse Comptonized after intercepted at the PSC and produces the spectral features of the black holes (Chakrabarti & Titarchuk 1995). In addition, PSC deflects a part of the accreting matter to produce bipolar jets and outflows due to the excess thermal gradient force present across the shock (Chakrabarti 1999;Das et al 2001b;Chattopadhyay & Das 2007;Das & Chattopadhyay 2008;Aktar et al 2015). When PSC modulates, quasiperiodic oscillation (QPO) of hard radiations in the spectral states is observed (Chakrabarti & Manickam 2000;Nandi et al 2001aNandi et al ,b, 2012 along with the variable outflow rates (Das et al 2001b).…”
Section: Introductionmentioning
confidence: 99%